Dictyoptera sex pheromones. Biology, Exocrine glands, Ethology - DAVID-HENRIET, ANA ISABEL; BROSSUT, RÉMY (Revista Colombiana de Entomología, 1995)
In the insects, odorant signals play an important role in the survival of the species. Cockroaches are gregarious insects. The approach of groups is assured by a gregarious pheromone which is secreted (in some species) by the jaw glands. These insects secret sexual pheromones which ensure the approach of both sexes and play an aphrodisiac role. In E. floridana, it’s the male that emits a sexual pheromone exposing a characteristic calling posture. This sexual pheromone emission by tergal glands allow the approach of both sexes: male and female touching their antennae, the male perceives, sometimes, a sexual contact pheromone present in the genital part of female or in her cuticular wax. The males expose the tergal glands of abdominal tergites 2, 7, and 8. It shakes its body side to side. The mature female approaches the male and opens her genitalia. She mounts on the male and backs to lick the tergal secretions emitted on tergite 1, where a tuft of setae can be seen. Finally, the male underneath the female, moves backward, thrusting upward his abdomen and protruding its phylloxera to make a connection with the genitalia of the female. Histological studies of different glandular regions showed that glands which produce the pheromone are of type III. The structure of the tuft of setae seems to be complex. The chemical identification reveals the presence of three principal compounds in the tergite 8: (2R-3R)-(-)butanediol, dodecanol, and benzyl-2-hydroxybenzoate); and a principal compound in the tergite 7 the 2,2-dimethyl-4-hydroxy-3(2H)-furanone "furaneol". No compounds were identified in the tergite 2.